Risk Factors for Neck Functional Ability in Esports Players - Wahyu Andriawan; Farid Rahman (JURNAL PENDIDIKAN JASMANI DAN OLAHRAGA, 2024)
The public's interest in the world of esports is increasing, both nationally and internationally. The current generation's participation, along with the government's support through prestigious competitions, is producing promising talents. The ambition to compete in esports games has caught the attention of researchers, as the process of engaging the body's functions can lead to physical problems that affect performance. Musculoskeletal disorders that occur involve the accumulation of various factors, which are considered disruptive to players. The highest reported prevalence of complaints is in the neck region, with varying levels of pain. The aim of this study is to determine the relationship and influence of age, gender, player type, duration of play, length of participation, and stress levels on the functional ability of esports players' necks. Through observational analytical research with a cross-sectional approach, researchers analyzed statistically to find the relationship and influence. The results showed that gender and stress level variables have a weak relationship and influence on the occurrence of neck disability. Meanwhile, the player type, age, duration of play, and length of participation variables do not seem to correlate with the functional ability of the neck.  Further research is needed on the effect of stress levels experienced by individuals that affect their physical performance in performing functional activities in the field of esports.